PIK Podziemny Informator Katowicki . biuletyn informacyjny Solidarności Walczącej - Oddział Katowice, no. 22, 1985 - Orwell, George; Morawiecki, Kornel (AISW, 1985)
Creation and circulation: Publication cooperated with Regionalna Komisja Koordynacyjna of the Śląsko-Dąbrowski region. In 1986-1987 suspended